HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN STATUS GIZI REMAJA PUTRI USIA 18-20 TAHUN MAHASISWI PROGRAM STUDI GIZI POLTEKKES KEMENKES KUPANG - kalitu, resta; Setia, Agustina; Demu, Yohanes Don Bosko (Kupang Journal of Food and Nutrition Research, 2024)
Adolescence is the stage of life that is between puberty and full maturity. This is also the time when a person matures physically from childhood to adulthood. A healthy diet must be followed to obtain good nutritional status through food consumption. The aim of a diet is to control the amount and type of food consumed in order to maintain nutritional status, improve health, and avoid or help treat disease. Lack of physical activity can cause excess weight. The aim of this research is to determine the relationship between eating habits, physical activity and nutritional status. Cross-sectional research with quantitative analysis is the type of research used. From the research results, it was found that the age distribution of teenagers with the highest frequency was 19 years old with a frequency of 66 people (44.9%), the distribution of food types in the moderate category with the highest frequency was 147 people (100.0%), the distribution of the frequency of eating in the moderate category with the highest frequency. 147 people (100.0), the physical activity category with the highest frequency was light activity 138 people (93.9%), the distribution of body mass index categories with the highest frequency was Normal weight 88 people (59.9%), and upper arm circumference with the highest frequency was the Normal category, 79 people (53.7%). From the results of this study, there was no relationship between diet and physical activity and nutritional status.